IDENTIFIKASI KESALAHAN PESERTA DIDIK KELAS V DALAM MEMECAHKAN SOAL HOTS MATEMATIKA BERDASARKAN PROSEDUR NEWMAN DI SDN 1 TAMBAKREJO - Ika Ayu Rerika Eritana; Suryatin; Tika Dedy Prastyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Evaluating student errors in solving Higher Order Thinking Skills (HOTS) mathematics problem is crucial, given the low level of advance computational thinking skills in elementary schools. This study utilized a descriptive-qualitative approach to map the errors made by 18 fifth-grade students at SDN 1 Tambakrejo in resolving mathematics HOTS problems concerning angle concepts based on Newman’s error analysis framework. Data were gathered through documentation, written test, and guided interviews. The analysis involved data reduction, data display, and conclusion drawning categorized into five components of Newman’s framework. The findings releaved that no reading errors were commited by the subjects. However, prominent obstacles were identified during the comprehension, transformation, process skills, and final answer-writing stages. The most dominant error type occurred within process skills, as evidenced by the students’ inability to perform calculations, apply appropriate procedures, and complete the mathematical solving steps.